2023
DOI: 10.3390/foods12112218
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Rheology of Olive Paste for Oil Extraction Plant Automation: Effects of the Crushing Process on the Rheology of Olive Pastes

Abstract: In extra virgin olive oil production, it is essential to obtain a well-prepared olive paste which allows not only the extraction of the oil drops from the olives, but also the achievement of a high-quality oil while maintaining high yields. This work addresses the problem of determining the effect of three crushing machines on the viscosity of the olive paste: a hammer crusher, a disk crusher and a de-stoner were tested. The tests were repeated on both the paste leaving each machine and the paste to which wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…The Pareto chart shows the absolute values of the standardized effects from the largest effect to the smallest effect. The results showed that the greatest variability depends on the fruit moisture content, in agreement with previous studies that relate the oil yield with fruit characteristics, such as ripening, pectic substances, and moisture and oil content ( Kalogianni et al., 2019 ; Perone et al., 2023 ). In addition, it can also be seen in the Pareto chart that the machinery, characterized by specific technological characteristics, and malaxation temperature are factors of great relative impact that must be taken into account when setting up the processing conditions ( Altieri et al., 2013 ; Esposto et al., 2013 ).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The Pareto chart shows the absolute values of the standardized effects from the largest effect to the smallest effect. The results showed that the greatest variability depends on the fruit moisture content, in agreement with previous studies that relate the oil yield with fruit characteristics, such as ripening, pectic substances, and moisture and oil content ( Kalogianni et al., 2019 ; Perone et al., 2023 ). In addition, it can also be seen in the Pareto chart that the machinery, characterized by specific technological characteristics, and malaxation temperature are factors of great relative impact that must be taken into account when setting up the processing conditions ( Altieri et al., 2013 ; Esposto et al., 2013 ).…”
Section: Resultssupporting
confidence: 91%
“…The results of pomace fat content showed average values ranging from 9% to 14% on a dry basis (db), reaching an extraction efficiency within the range of 78%–91%, in agreement with the results of oil extractability reported in other studies for the ‘Arbequina’ cultivar ( Boudebouz et al., 2021 ; Hermoso et al., 2021 ; Khaleghi et al., 2023 ; Perone et al., 2023 ). It must be pointed out that, during virgin olive oil production, oil losses of up to 10% through pomace are traditionally accepted for this variety.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations